2010
DOI: 10.1002/jcb.22599
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel tropomyosin isoform in axolotl heart and skeletal muscle

Abstract: TPM1κ is an alternatively spliced isoform of the TPM1 gene whose specific role in cardiac development and disease is yet to be elucidated. Although mRNA studies have shown TPM1κ expression in axolotl heart and skeletal muscle, it has not been quantified. Also the presence of TPM1κ protein in axolotl heart and skeletal muscle has not been demonstrated. In this study, we quantified TPM1κ mRNA expression in axolotl heart and skeletal muscle. Using a newly developed TPM1κ specific antibody, we demonstrated the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 16 publications
(23 reference statements)
2
52
0
Order By: Relevance
“…On the other hand the relative expression of TPM1κ is higher in the heart. The results are consistent with our reported findings in mice (Dube et al, 2014), and axolotl (Thomas et al, 2010). However, when we compared the absolute copy number expression in heart and skeletal muscle, the expression of TPM1α compared to TPM1κ is much higher (~300 fold) in heart.…”
Section: Figsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand the relative expression of TPM1κ is higher in the heart. The results are consistent with our reported findings in mice (Dube et al, 2014), and axolotl (Thomas et al, 2010). However, when we compared the absolute copy number expression in heart and skeletal muscle, the expression of TPM1α compared to TPM1κ is much higher (~300 fold) in heart.…”
Section: Figsupporting
confidence: 92%
“…However, the functional role of TPM1κ is yet to be established. It is known that TPM1κ is ~5% of the total sarcomeric tropomyosin protein in human hearts, which is also true for axolotl (Thomas et al, 2010). We already reported that an anti-sense mediated down regulation of TPM1κ inhibited the cardiac contractility in axolotl in situ suggesting a critical role of TPM1κ protein in cardiac contractility.…”
Section: Figmentioning
confidence: 79%
See 1 more Smart Citation
“…The copy number per volume of clone in solution was determined using the equation number of copies = (ng of plasmid DNA × 6.02 × 10 23 )/(bp length of plasmid × 1 × 10 9 × 650), which was simplified by Andrew Staroscik at the URI Genomics and Sequencing Center. A dilution series of each clone was done for 1 × 10 1 −1 × 10 4 copies of template, which was used to create a standard curve after amplification (Figure 6) (Dube et al, , ; Thomas et al, ; Thurston et al, ). For better accuracy, each sample in the dilution series was run in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Axolotls are commonly employed in biomedical research due to their ability to quickly repair damaged tissues (Voss and Shaffer, 1997;Wakahara, 1996). Indeed, most studies of the axolotl heart focus on its ability to regenerate after partial ventricular amputation (Cano-Martínez et al, 2010) or on sarcomeric proteins mutations (Thomas et al, 2010;Ward et al, 1995). Given their relevance for biomedical research, it is surprising that very little is known about the intrinsic contractile properties of the axolotl heart.…”
Section: Introductionmentioning
confidence: 97%